School Management Strategy and Synergy with the School Committee in Improving the Quality of Education at UPT SMA Negeri 20 Bone - Yandi Pratama; Hasniaty Hasniaty, Mujahid Mujahid, Sri Adrianti (Pascasarjana STIE Amkop Makassar, 2026)
This study aims to analyze the school management strategy implemented in SMA Negeri 20 Bone and examine the synergy between the school and the school committee in improving the quality of education. The approach used is qualitative by involving key informants, namely the Principal, Teachers, administrative staff, and the School Committee.The results of the study indicate that strategies for improving the quality of education at SMA Negeri 20 Bone include: (1) Improving the competence of the principal through educational leadership training and quality-based management; (2) Active involvement of teachers in the school program planning process and curriculum development based on student needs; (3) Improvement of the administration system through the application of information technology to increase efficiency and transparency; and (4) Continuous evaluation to monitor the effectiveness of the strategies implemented.In addition, synergy between schools and school committees is an important factor in encouraging improvements in the quality of education. School committees act as strategic partners by carrying out several main functions, namely: (1) Providing input and supervision of school budget planning and management; (2) Facilitating collaboration between schools and the community, including industry partners and other educational institutions; (3) Initiating supporting programs such as student skills training, career seminars, and extracurricular development; and (4) Monitoring transparency and accountability in the management of school funds and policies.This finding confirms that improving the quality of education at SMA Negeri 20 Bone requires close and continuous collaboration between the school and the school committee. By implementing a structured management strategy and strengthening the role of the school committee, it is expected to create an effective and conducive learning environment for student development.Keywords: Strategy, School Management, Synergy, School Committee, Quality of Education